Utilization Of Hoogere Kweekschool (HKS) Purworejo Cultural Heritage as Strengthening Students' Pancasila Dimensional Profile in History Learning - Damaringtyas, Christophorus Putro; nazara, Ranita; Aman, Aman (Diakronika, 2024)
This study aims to determine the potential utilization of cultural heritage in SMA Negeri 7 Purworejo, strengthening the six dimensions of the Pancasila Student Profile. This research uses a qualitative approach and a type of field study research. Data was obtained through observation, interviews and literature studies. This research was conducted at SMA Negeri 7 Purworejo, the Ex Hoogere Kweekschool (HKS) Purworejo. The investigation results show that the utilization of the former HKS Purworejo building can be a medium to strengthen the six dimensions of the Pancasila Student Profile because it contains harmonious historical values and moral messages regarding the matters contained in Pancasila. The selection of learning resources around the student's environment provides real experience in delivering historical material, so students have a sociocultural and emotional connection with the material presented. It can also enrich local history learning resources in Purworejo Regency.